Majaz dalam Novel Yaum Qutila al-Za‘īm Karya Najib Mahfuz: Kajian Ilmu Bayan: Metaphor in the Novel Yaum Qutila al-Za‘īm by Naguib Mahfouz: A Study of Bayan - Azra; Fadlil; Rohanda (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
This study aims to analyze the use of metaphor in the novel Yaum Qutila al-Za‘īm by Naguib Mahfouz using the science of bayan. A qualitative descriptive method was employed. The research data consisted of the Arabic-language novel text containing metaphors. Data collection was conducted through note-taking and documentation. Data presentation was conducted using maximum variation sampling, while data analysis involved the stages of identifying, classifying, and describing the types and purposes of metaphor based on metaphor theory. The results indicate that various types of metaphor were found in the novel, namely aqli as-sababiyah, aqli az-zamaniyyah, isti‘arah makniyyah, isti‘arah taṣrīḥiyyah, isti‘arah tamṡīliyyah, mursal al-mahalliya, mursal al-juziyyah, mursal as-sababiyyah, mursal al-āliyyah, mursal al-lazimiyah, mursal itibar ma yakunu, and mursal al-kulliyah. Furthermore, the use of metaphor in this novel serves not only as an aesthetic element but also fulfills rhetorical purposes, namely ta’kīd al-ma‘nā and tabyīn al-ma‘nā. These findings indicate that Naguib Mahfouz employs metaphor as an expressive strategy to convey ideas, emotions, and social criticism in a more profound and implicit manner. Thus, metaphor in this work plays a crucial role in constructing the complexity of meaning and enriching the dimensions of the reader’s interpretation of modern Arabic literary texts.